Effect of Phosphorus on the Activity and Stability of Supported Cobalt Catalysts for Fischer‐Tropsch Synthesis. Issue 17 (1st August 2018) - Martinelli, Michela; Kumaran Gnanamani, Muthu; Hopps, Shelley D.; Sparks, Dennis E.; MacLennan, Aimee; Hu, Yongfeng; Davis, Burtron H.; Jacobs, Gary
Abstract: Phosphorus promotion on Fischer‐Tropsch (FT) synthesis was investigated for Co/Al2 O3 and Co/SiO2 catalysts having the same Co/P ratio. When P is added to Co/Al2 O3, CO conversion on a per g catalyst basis decreased, while methane selectivity increased. Catalyst stability was higher for the sample containing both P and Pt. The main cause for lower initial conversion is Co site blocking, while the lower extent of cobalt reduction for the P‐promoted Co/Al2 O3 sample played a lesser role. When SiO2 is used to support cobalt particles, an initial induction period for the P‐promoted catalyst was observed, where CO conversion increased. Higher CO conversion at steady state, as well as improved catalyst stability during FT testing, suggest that P hindered sintering. Over the same period, a decline and leveling off of conversion were observed for the unpromoted catalyst. Completely different effects were observed depending on support type. P only acted as a poison for Co/Al2 O3, whereas beneficial effects on steady state CO conversion and stability occurred with Co/SiO2 . The different effects of P for Al2 O3 and SiO2 supported Co catalysts can be explained by differences in Co‐support interactions. With alumina, Co clusters are already stabilized by strong interactions with the support. P has no benefit, as it mainly interacts with alumina instead of Co; pore blocking by P also occurred. In contrast, SiO2 has weak interactions with Co and less Co cluster stabilization. With P promotion, P anchors Co to the support, improving Co dispersion, stability and steady‐state conversion. Abstract : Interactions matter : Phosphorus addition to cobalt Fischer‐Tropsch synthesis catalysts depends on metal‐support interactions. There was no benefit with strongly interacting alumina; P interacts with the support. In contrast, with weakly interacting silica, P anchors cobalt to the support, improving dispersion, stability and steady‐state conversion.